The Role of the Notary/PPAT in Process Transfer of Land Functions From Agricultural Land Into Non-Agricultural Land in Demak District Land Office - Budi Santosa; Muslich Ashari; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study is as follows: 1) To determine the role of the Notary PPAT in the process of the transfer function of soil from agricultural to non-agricultural land in the District Land Office Demak.2) To know the obstacles in the process of soil functions from agriculture to non-agricultural land in the Land Office District Demak.3) .To find out a solution to the obstacles in the process of the transfer function of soil from agricultural to non-agricultural land in Demak District land Office.Methods using sociological juridical approach, Research Specs, Types and Sources of Data, Data Collection Methods, Technical Analysis.Based on the results of the study concluded that the procedure of land transfer function of agriculture to non-agricultural land in the National Land Office Demak, do the applicant by way of location permits, licenses and land use permits land use changes. Factors to be an obstacle in the procedure of the transfer function of the land from agricultural land to non-agricultural in the Office of the National Land Demak and how to overcome among others: the permissions that are not in accordance with the plan of spatial Demak, settlement efforts in addressing licensing should be transparent and in accordance with the regional spatial plan Demak. Suggestions Should the Office of the National Land Demak apply policy rules corresponding spatial Demak district in order to avoid the equalizing impact of underdevelopment in the region of Demak, therefore the application mechanism location permits, permit the use of land and permission changes in land use were tightened in order transition of agricultural land into non-agricultural destructive to the environment of Demak.Keywords: Notary / PPAT, Transfer of Functions Land, Agricultural Land to Non-Agricultural.